Formation universitaire et insertion professionnelle : une enquête sur l’expérience des diplômés universitaires en langue française au Nigéria - Tajudeen Abodunrin Osunniran; Mohammed Sale Also (Multilinguales)
This study examines the professional situation of French language graduates in Nigeria. It explores, among other things, the main sectors providing employment to these graduates, the challenges they face in the process of integration and their perceptions of the adequacy between the training provided in departments of French across Nigerian Universities and the needs of an Anglophone labour market. The data of the study was collected through a questionnaire from 143 respondents who graduated between 2007 and 2017. The results of the study show that there is a low penetration of French language graduates into the business world. These graduates, given the training received, seem more likely to find work in education. They unanimously support a reform of the French program in order to widen the range of opportunities they can have access to in the labour market.